AVALIAÇÂO DA RESISTÊNCIA DO SOLO A PENETRAÇÃO COM PENETRÔMETRO DE IMPACTO E PENETRÔMETRO DIGITAL - MACHADO, Cauã Melo; BONFIM, Willian Gabriel Alves; MARCANZONI, Bruno Ito; GOTTARDI, Guilherme Alves; RICARDO, Victor Gabriel de Souza; ZOZ, Tiago (ANAIS DO ENIC, 2026)
.